The Effect of Education with T-Plate Modeling on Mothers' Knowledge about Obesity Diet - Agustina, Venti; Nurhayati; Herlina, Lily; Khasanah, Uswatul (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2025)
The GENTAS program (Gerakan Nusantara Tekan Angka Obesitas) recommends the use of the T plate model in one of its programs to reduce the prevalence of obesity. He purpose of this study was to determine the effect of education with T plate modeling on maternal knowledge about obesity diet. This study used a quasi-experiment with a one-group pretest-posttest approach, involving 18 mothers from RW 04,05, and 06 Harapan Mulya Village, Kemayoran District, Central Jakarta. Mothers' knowledge was measured using a questionnaire on obesity diet management knowledge given before and after education using the T-shaped Plate modeling. Data analysis used the Wilcoxon Test technique with a p-value of 0.05. Data analysis using Jamovi 2.3.28 software. The results of the analysis using the Wilcoxon test obtained the t value on the obesity diet knowledge variable, both pre-test and post-test, with a p-value of 0.001 (p <0.05) and an effect size of -1.00. This means that there is an effect of education with T plate modeling on obesity diet knowledge before and after intervention. ABSTRAK Program GENTAS (Gerakan Nusantara Tekan Angka Obesitas) menganjurkan penggunaan piring makan model T dalam salah satu gerakannya untuk menurunkan prevalensi obesitas. Tujuan penelitian ini adalah mengetahui pengaruh edukasi dengan pemodelan Piring T terhadap pengetahuan ibu mengenai diet obesitas. Penelitian ini menggunakan quasi-experimen dengan pendekatan one group pretest postest, yang melibatkan 18 ibu dari RW 04,05, 06 Kelurahan Harapan Mulya, Kecamatan Kemayoran, Jakarta Pusat. Pengetahuan ibu diukur menggunakan kuesioner pengetahuan pengelolaan diit obesitas yang diberikan sebelum dan sesudah edukasi menggunakan pemodelan Piring T. Analisis data menggunakan teknik Uji Wilcoxon dengan p-value 0,05 Analisis data dengan menggunakan software Jamovi 2.3.28. Hasil analisa dengan menggunakan uji Wilcoxon diperoleh nilai t hitung pada variabel pengetahuan diet obesitas baik pre-test dan post-test dengan p-value 0,001(p< 0,05) dan effect size -1,00. Hal ini mempunyai arti bahwa terdapat pengaruh edukasi dengan pemodelan Piring T terhadap pengetahuan diit obesitas sebelum dan sesudah intervensi.